1973
DOI: 10.1104/pp.51.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Endosperm Protein of Wheat Seed as a Determinant of Seedling Growth

Abstract: Seed of a Mexican semidwarf wheat (Triticum aestivum L. cv. Inia 66), was obtained from a nitrogen fertilizer field trial grown in Mexico. A high positive correlation was obtained between seed protein content and seedling dry weight after 3 weeks growth (r = +0.92**). The seedling dry weight was positively related to the protein content of the aleurone layer and endosperm, but not to the embryo. Small, 35 Studies have shown that seed source, size, and protein content of both monocotyledonous and dicotyledono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Since the seeds were not submitted to stress, were not subjected to different storage conditions, and were not imbibed when sampled, the greater quantity of albumins in lot 24 can only indicate that this difference arose during seed development. Differences in seed soluble protein content have been determined to contribute to altered seed vigour previously (Lowe and Ries, 1973;Strelec et al, 2007;Borba et al, 2014) and seed storage reserve amounts, including protein, are known to be influenced by the maternal parent (Letchworth and Lambert, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the seeds were not submitted to stress, were not subjected to different storage conditions, and were not imbibed when sampled, the greater quantity of albumins in lot 24 can only indicate that this difference arose during seed development. Differences in seed soluble protein content have been determined to contribute to altered seed vigour previously (Lowe and Ries, 1973;Strelec et al, 2007;Borba et al, 2014) and seed storage reserve amounts, including protein, are known to be influenced by the maternal parent (Letchworth and Lambert, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids produced from hydrolysis of the storage proteins can also be deaminated and, along with starch and lipid reserves, catabolized for energy production. In this way, greater storage reserve amounts in seeds can result in seedlings with greater vigour (Lowe and Ries, 1973;Bortolotto et al, 2008;Carvalho and Nakagawa, 2012). In addition, problems realizing full physiological potential in seeds can lead to poor desiccation tolerance (Hay and Probert, 1995;Faria et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A habilidade das sementes grandes em produzir plântulas maiores é mais pronunciada em condições de baixa disponibilidade hídrica (Mian & Nafziger, 1994), alta salinidade (Grieve & Francois, 1992), semeadura profunda (Mian & Nafziger, 1994) ou baixo suprimento de N pelo solo, aumentando, assim, a importância das reservas da semente como fonte de nutrientes para o crescimento inicial da planta (Lowe & Ries, 1973). O tamanho da semente, em muitas espécies, é indicativo de sua qualidade fisioló-gica (Popinigis, 1977).…”
Section: Introductionunclassified
“…Seed nitrogen content is also an important determinant. It was reported that the increase of seed nitrogen content enhanced the seedling growth (Fox and Albrecht 1957;Schweizer and Ries 1969;Lowe and Ries 1973;Metivier and Dale 1977;Rahman and Goodman 1983;Lieffering et al 1996;Hara and Toriyama 1998). However, to our knowledge, there are no reports on the effect of seed nitrogen content on the percentage of establishment except a report on wheat (Fox and Albrecht 1957).…”
mentioning
confidence: 97%